Peer Observation of Teaching as an approach for School based Teacher Professional Development: Minghang Senior High School Teachers’ Perspectives - Abdalla, Alsiddig Ismail Mohammed (Journal of Faculty of Education, 2021)
Teacher professional development is regarded as one of the key factors that help in achieving quality in education, especially in the developing and less developed countries where a large number of teachers do not have any teacher education, and education institutions are still dependent to great extent on the traditional methods in teacher preparation. This study mainly aimed at exploring (Minhang Senior High School – Shanghai - China) teachers’ views on using peer observation of teaching as an approach for school based professional development and knowing the extent of its effectiveness in enhancing teaching practice according to their views. As it also aimed at investigating the extent of teachers’ perception for how peer observation of teaching is done.